The Production Function: A New Perspective in Capital Maintenance. - Petri, Enrico; Gelfand, Jack (The Accounting Review, 1979)
ABSTRACT: This paper presents a conceptual analysis of two views of output maintenance using the tools of µ-economic theory. The analysis highlights the significance of factor substitution as an essential element in calculating replacement cost. Within this theoretical framework, sales price and cost change are analyzed to determine the relevance of their impact on factor input ratios and output isoquants for both single- and multi-product firms.